CO2 = CO + O: Redox-Neutral Lactamization and Lactonization of C–H Bonds with CO2 - Zhang, Zhen; Ju, Tao; Ye, Jian-Heng; Yu, Da-Gang (Synlett, 2017)
Carbon dioxide, a nontoxic, cheap and readily available greenhouse gas, acts as the ideal carbonyl source with similar function as the combination of CO and oxidants (‘CO2 = CO + O’). We highlight this concept with recent advances of the lactamization and lactonization of C–H bond with CO2 under redox-neutral or even transition-metal-free conditions.
Keywords: carbon dioxide; lactamization; lactonization; C–H bond functionalization; redox neutral